Oral propranolol therapy in parotid hemangiomas: A retrospective comparison with other infantile hemangiomas. Issue 5 (4th February 2021) - Wang, Luying; Li, Shaohua; Gao, Qianqian; Lv, Renrong; Xu, Guangqi; Li, Xueqing; Bi, Jianhai; Huo, Ran
Abstract: Background: The outcomes of propranolol treatment remain controversial for parotid hemangiomas, which may be inferior to outcomes for infantile hemangiomas (IHs) at other sites. Methods: Patients with IHs treated with oral propranolol were retrospectively reviewed. Outcomes of propranolol therapy for parotid hemangiomas and other IHs were examined. Regression models were conducted to analyze the factors associated with the outcomes for parotid hemangiomas. Results: Longer treatment duration was needed for parotid hemangiomas ( p = 0.012) at a comparable efficacy and relapse rate as those of IHs at other sites. The higher efficacy was associated with early intervention before 4 months of age (OR = 5.2, p = 0.011), while, the lower relapse rate was associated with adequate treatment duration over 6 months (OR = 9.2, p = 0.010). Conclusions: With a longer propranolol treatment duration, parotid hemangiomas could achieve a comparable efficacy and relapse rate as other IHs. Early treatment initiation and adequate treatment duration benefited the outcomes.